Existence of Solution to a Second-Order Boundary Value Problem via Noncompactness Measures - Wen-Xue Zhou; Jigen Peng (Discrete Dynamics in Nature and Society)
The existence and uniqueness of the solutions to the Dirichlet boundary value problem in the Banach spaces is discussed by using the fixed point theory of condensing mapping, doing precise computation of measure of noncompactness, and calculating the spectral radius of linear operator.